QiShenYiQi pill for myocardial collagen metabolism and apoptosis in rats of autoimmune cardiomyopathy - Shichao Lv; Wanqin Zhang; Peng Yuan; Chunmiao Lu; Jianping Dong; Junping Zhang (Taylor & Francis Group, 2022)
Context QiShenYiQi pill (QSYQ) is a traditional Chinese medicine with a myocardial protective effect.Objective To explore the effect of QSYQ on myocardial collagen metabolism in rats with autoimmune cardiomyopathy and explore the underlying mechanism from the aspect of apoptosis.Materials and methods We established an autoimmune cardiomyopathy model using Lewis rats. The rats were then randomly divided into six groups (n = 8): control, model, 3-methyladenine (15 mg/kg, intraperitoneal injection), QSYQ low-dose (135 mg/kg, gavage), QSYQ medium dose (270 mg/kg, gavage), and QSYQ high-dose (540 mg/kg, gavage) for four weeks. Van Gieson staining was applied for myocardial pathological characteristics, TUNEL fluorescence for myocardial cell apoptosis, enzyme-linked immunosorbent assay (ELISA) for serum PICP, PIIINP, and CTX-I levels, and western blot analysis for type I/III myocardial collagen, Bcl-2, Bax, and caspase-3 proteins.Results Results showed that QSYQ (135, 270, or 540 mg/kg) significantly reduced the expression of myocardial type I/III collagen, and concentrations of serum PICP, PIIINP, and CTX-I in rats. Moreover, QSYQ could alleviate myocardial fibrosis more effectively at a higher dose. QSYQ could also inhibit myocardial apoptosis via downregulating Bcl-2 expression, and upregulating Bax and caspase-3 expression levels.Discussion and conclusions The QSYQ can improve myocardial collagen metabolism by inhibiting apoptosis, which provides a potential therapeutic approach for autoimmune cardiomyopathy.